Development and Validation of Simultaneous UV Spectrophotometric Method for Estimation of Paracetamol and Nimesulide in Tablet Dosage Form - Rupali Kirtawade; Pallavi Salve; Chhotaram Seervi; Anita Kulkarni; Pandurang Dhabale (Challenges and Advances in Pharmaceutical Research Vol. 7, 2022)
New, rapid, economical and simple spectrophotometric methods were investigated for the estimation of paracetamol and Nimesulide in combined tablet dosage forms. Nimesulide is a nonsteroidal anti-inflammatory drug, and paracetamol is an analgesic and antipyretic. Procedures for simultaneous estimation of Paracetamol and Nimesulide in tablet dosage form that are simple, accurate, precise, reproducible, do not require prior separation, and are cost effective have been developed. Method employs formation and solving of simultaneous equation using 245.5 nm and 299.5 nm as two analytical wavelengths for both drugs in methanol-Distilled water (50:50). Paracetamol and Nimesulide at their respective \(λ\)max 245.5 nm and 299.5 nm shows linearity in a concentration range of 1-11 \(μ\)g /mL and 5-30\(μ\)g /mL. Recovery studies for Paracetamol were 99.56% and 100.14% for Nimesulide, respectively, confirming the accuracy of the proposed method. The proposed method is appropriate for routine analysis because it is quick, simple, accurate, sensitive, and specific.